Pengaruh Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian Kendaraan Bermotor Merk Honda (Studi Kasus Konsumen Pengguna Merk Honda) - Eryanawati Eryanawati; Ismunandar Ismunandar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
This research was conducted because there is competition between brands, to prevent competition, each producer must create a quality product arena that is found at this time lacking one of the advantages of a product being promoted, consumers will move to other brands. This research aims to find out how much influence product quality and promotion of the decision to purchase Honda motor vehicles tested through SPSS 16.0. The type of research used is Associative, this study was conducted on DEALER ASTRA MOTOR BIMA. The population in this study were all Honda brand motorcycle users with 96 samples people using random sampling techniques. In the initial testing conducted that the indicator of each variable used states valid for measuring each variable, the next stage shows that the value of the variable for product quality is 0.879 while the promotional variable is 0.929, which means that promotion has a more dominant influence on the decision to buy Honda motor vehicles